The Relationship between Epicardial Fat Thickness and Endothelial Dysfunction in Type I Diabetes Mellitus. (27th April 2015) - Aslan, Abdullah Nabi; Keleş, Telat; Ayhan, Hüseyin; Kasapkara, Hacı Ahmet; Akçay, Murat; Durmaz, Tahir; Sarı, Cenk; Baştuğ, Serdal; Çakır, Bekir; Bozkurt, Engin
Abstract : Background and Aim: Epicardial adipose tissue (EAT) is a new independent marker of coronary artery disease (CAD). The aim of this study was to investigate the relationship between epicardial fat thickness (EFT) and endothelial dysfunction (ED) in patients with type I diabetes mellitus (TIDM). Methods and Results: Seventy‐six type I diabetic patients (diabetes duration 11.7 ± 8, 1 years, aged 30.6 ± 10 years; female/male: 38/38) and 36 healthy controls were enrolled into the study. Fasting plasma glucose (FPG), lipid panel, glycosylated hemoglobin (HbA1C), high‐sensitive C‐reactive protein (hsCRP), and fibrinogen levels were determined. EFT was measured via two‐dimensional (2D) M‐mode echocardiography. Endothelial function was assessed as flow‐mediated dilatation (FMD) at the brachial artery using high‐resolution ultrasound. EFT was significantly higher in patients compared to controls (3.56 ± 0.48 mm vs. 3.03 ± 0.48 mm, P < 0.001). In addition, significant differences were observed between the patient and control groups in terms of FMD (6.70% ± 1.63 vs. 9.99% ± 1.84, respectively, P < 0.001). EFT was shown to be correlated negatively with FMD (r: −0.94, P < 0.001) and positively with hsCRP (r: 0.41, P < 0.001) and fibrinogen (r: 0. 31, P = 0.007). Multiple regression analysis showed EFT to be an independent factor influencing the endothelial function. Conclusion: There was inverse relationship between EFT and endothelial function in this study. EFT measured easily by transthoracic echocardiography may be a useful parameter in the assessment of patients with TIDM.